2006
DOI: 10.1136/ard.2006.051649
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in gout epidemiology: evaluation and treatment

Abstract: Background: Little is known about the characteristics, evaluation and treatment of women with gout. Objective: To examine the epidemiological differences and differences in treatment between men and women in a large patient population. Methods: The data from approximately 1.4 million people who were members of seven managed care plans in the USA for at least 1 year between 1 January 1999 and 31 December 2003 were examined. Adult members who had pharmacy benefits and at least two ambulatory claims specifying a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1
30

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 16 publications
8
100
1
30
Order By: Relevance
“…Similarly, we found that 24% of patients received uric acid monitoring within 6 months of new allopurinol prescription, and 2 studies in managed care plans found analogous rates of 37% (17) and 13% (18). The former study found that women were more likely than men to receive serum urate monitoring (17), implying that quality of gout care may vary by sex.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, we found that 24% of patients received uric acid monitoring within 6 months of new allopurinol prescription, and 2 studies in managed care plans found analogous rates of 37% (17) and 13% (18). The former study found that women were more likely than men to receive serum urate monitoring (17), implying that quality of gout care may vary by sex.…”
Section: Discussionmentioning
confidence: 97%
“…Mikuls et al examined 3 QIs in the UK General Practitioner Research Database (UKGPRD) and found low (25-57%) physician adherence (16). Studies in US health plans have found gaps in quality care for gout (17,18). It is unknown whether care provided to US veterans with gout meets these minimum quality standards.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the general medical population have shown a higher risk for gout in older postmenopausal women, as well as women with CKD. [23][24][25] An effect of estrogen to reduce uric acid levels needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…В сред-нем дебют подагры у них развивался спустя всего 3,7 [2,3; 6,0] года после прекращения менструаций. Обсуждение К настоящему времени опубликовано всего несколь-ко исследований, посвященных анализу половых различий факторов риска развития гиперурикемии и подагры [5,8,10]. Общим для всех этих исследований был значительно больший средний возраст больных подагрой женщин, что во многом предопределяло и большую частоту выявления у них некоторых факторов риска гиперурикемии и подаг-ры.…”
Section: результатыunclassified